Punjabi Speech Synthesis System for Android Mobile Phones (International Journal of Engineering and Computer Science, 2014)
Mobile phone usage is approximately 3.5 times more than the usage of Personal Computers. Android has the biggest share among all Smartphone Operating systems like Symbian, Windows etc. because it has very few restrictions for the developers to develop an application. Text to speech synthesis is one application which reads the written text aloud. TTS systems on Android are available for many languages but not for Punjabi. Our present work is to develop a Punjabi text to speech synthesizer that can produce an output speech on a mobile device. While porting this TTS system to a resource limited device like mobile phones, some practical aspects like application size and processing time are considered. The Concatenative Speech Synthesis technique has been used which uses the Phonemes as the smallest single units for concatenation.